Views on the Issue of Accountability in Non-Profit Organizations (Malaysian Management Journal, 2010)
Over the past few decades, concerns have been raised about the accountability of non-profit organizations, especially on the adequacy of the current reporting and oversight mechanisms. Non-profit organizations are now increasingly demanded to become more accountable and demonstrate that they are making a difference and delivering results. However, the issues of non-profit accountability are problematic and more complex as compared to business organisations. As such, in this paper, pertinent issues of accountability in NPO are discussed. This is done by discussing the unique nature of non-profit organisations and their conflicting demands for accountability. The paper also elaborates the complex relationship of trust and its consequences and influences on the informal and also formal forms of accountability, specifically on the use of financial reporting.